2023
DOI: 10.1126/sciadv.adg0478
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Piezo1 promotes osteogenic differentiation of aortic valve interstitial cell through YAP-dependent glutaminolysis

Abstract: Hemodynamic overload and dysregulation of cellular metabolism are involved in development of calcific aortic valve disease (CAVD). However, how mechanical stress relates to metabolic changes in CAVD remains unclear. Here, we show that Piezo1, a mechanosensitive ion channel, regulated glutaminase 1 (GLS1)–mediated glutaminolysis to promote osteogenic differentiation of valve interstitial cells (VICs). In vivo, two models of aortic valve stenosis were constructed by ascending aortic constriction (AAC) and direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Piezo1 mediates distinct Ca 2+ signaling pathways to regulate cellular activities [ 9 ]. Yes-associated protein (Yap) has been shown to be an important downstream mechanotransduction effector of Piezo1 [ 43 ]. A recent study showed that the double-knockout of Yap/Taz in smooth muscle significantly downregulated the expression of colonic motility-related genes (such as Tpm1, Actg2, Acta2) and impaired colonic contractility, causing colonic pseudo-obstruction and lethality [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Piezo1 mediates distinct Ca 2+ signaling pathways to regulate cellular activities [ 9 ]. Yes-associated protein (Yap) has been shown to be an important downstream mechanotransduction effector of Piezo1 [ 43 ]. A recent study showed that the double-knockout of Yap/Taz in smooth muscle significantly downregulated the expression of colonic motility-related genes (such as Tpm1, Actg2, Acta2) and impaired colonic contractility, causing colonic pseudo-obstruction and lethality [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…no. bes5001, Guangzhou Bersinbio Co., Ltd.) was used with slight modifications to the manufacturer's protocol ( 18 ). Cells were crosslinked using 1% formaldehyde and the reaction was terminated by adding glycine to a final concentration of 0.125 M. The E2F1 antibodies (1:100) were used to immunoprecipitate DNA from sonicated cell lysates, with IgG (BD Biosciences) as the negative control.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Zhong et al verified that Piezo1 activated by mechanical stress was able to regulate glutaminase 1 (GLS1)-mediated glutaminolysis and advance osteogenic differentiation of valve interstitial cells, whereas inhibition or knockdown of Piezo1 and GLS1 respectively diminished these effects. Mechanistically, activation of Piezo1 promoted calciumdependent YAP activation, thereby regulating GLS1-mediated glutaminolysis and enhancing osteogenic differentiation through histone acetylation of runt-related transcription factor 2 promoter [38]. Another study by Li suggested that mechanical stress accelerated the osteogenesis and angiogenesis of tissueengineered laminae through the F-actin/YAP-1/β-Catenin signaling axis.…”
Section: Hippo/yap and Regenerationmentioning
confidence: 99%